2019
DOI: 10.1016/j.bja.2018.10.065
|View full text |Cite
|
Sign up to set email alerts
|

BU10038 as a safe opioid analgesic with fewer side-effects after systemic and intrathecal administration in primates

Abstract: BACKGROUND: The marked increase in misuse and abuse of prescription opioids has greatly affected our society. One potential solution is to develop improved analgesics which have agonist action at both mu opioid peptide (MOP) and nociceptin/orphanin FQ peptide (NOP) receptors. BU10038 is a recently identified bifunctional MOP/NOP partial agonist. The aim of this study was to determine the functional profile of systemic or spinal delivery of BU10038 in primates after acute and chronic administration. METHODS: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 55 publications
(41 reference statements)
1
57
1
Order By: Relevance
“…7 In preclinical pain models, these compounds showed potent antinociceptive effects with favorable side effect profiles, including reduced or lack of respiratory depression, reinforcing effects, physical dependence, and tolerance development. [6][7][8] In comparison with these nociceptin/μ receptor partial agonists, cebranopadol stands out as a unique mixed nociceptin/opioid receptor agonist which displays full efficacy at μ, nociception, and δ receptors, and partial efficacy at κ receptors. 12,13 The antinociceptive effects of cebranopadol have been demonstrated in various rodent pain models.…”
Section: Cebranopadol In Nonhuman Primatesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In preclinical pain models, these compounds showed potent antinociceptive effects with favorable side effect profiles, including reduced or lack of respiratory depression, reinforcing effects, physical dependence, and tolerance development. [6][7][8] In comparison with these nociceptin/μ receptor partial agonists, cebranopadol stands out as a unique mixed nociceptin/opioid receptor agonist which displays full efficacy at μ, nociception, and δ receptors, and partial efficacy at κ receptors. 12,13 The antinociceptive effects of cebranopadol have been demonstrated in various rodent pain models.…”
Section: Cebranopadol In Nonhuman Primatesmentioning
confidence: 99%
“…5 Mounting evidence strongly suggests that the coactivation of the nociceptin and μ receptors might provide synergistic analgesic effects and simultaneously counteract μ receptor-mediated side effects. [6][7][8][9][10] Mixed nociceptin/μ receptor agonists are currently being pursued as promising novel analgesics.Several mixed nociceptin/μ receptor agonists have been reported. BU08028 and BU10038 bind with reasonable…”
mentioning
confidence: 99%
“…In this issue of the British Journal of Anaesthesia, Kiguchi and colleagues 16 describe a novel naltrexone derivative, BU10038, that is a MOP and NOP partial agonist; see Table 1 for comparison with existing mixed ligands. The authors show that systemic administration of BU10038 (i) produces long-lasting (24 h) antinociceptive and antiallodynic effects that are more potent than morphine, (ii) has a lack of reinforcing effects, a marker for abuse potential, (iii) lacks respiratory and cardiovascular side-effects, (iv) lacks physical dependence, and (v) does not produce tolerance.…”
mentioning
confidence: 99%
“…Ciccocioppo et al [ 240 ] found that buprenorphine, a partial agonist at MOP [ 240 ] and NOP receptors [ 241 , 242 ], has the ability to attenuate ethanol consumption in rats at high concentrations. Moreover, unlike buprenorphine, certain recently developed bifunctional NOP/MOP partial agonists (i.e., BU08028, BU10038, and AT-121) do not exhibit reinforcing effects in non-human primates [ 243 , 244 , 245 ]. These compounds selectively attenuate alcohol intake (BU08028) [ 246 ] and significantly attenuate oxycodone-induced reinforcing effects (daily systemic AT-121 pretreatment) [ 244 ] without disrupting food-maintained operant behavior.…”
Section: Anti-opioid Peptides: Potential Therapeutic Interestmentioning
confidence: 99%
“…Moreover, unlike buprenorphine, certain recently developed bifunctional NOP/MOP partial agonists (i.e., BU08028, BU10038, and AT-121) do not exhibit reinforcing effects in non-human primates [ 243 , 244 , 245 ]. These compounds selectively attenuate alcohol intake (BU08028) [ 246 ] and significantly attenuate oxycodone-induced reinforcing effects (daily systemic AT-121 pretreatment) [ 244 ] without disrupting food-maintained operant behavior. Furthermore, recently, two independent studies have demonstrated that cebranopadol, another NOP and MOP receptor agonist, is efficacious in attenuating the motivation for cocaine in drug self-administration studies, while leaving unaffected (or slightly increased) the consumption of natural rewards [ 247 , 248 ].…”
Section: Anti-opioid Peptides: Potential Therapeutic Interestmentioning
confidence: 99%